FORMULASI DAN UJI KARAKTERISTIK FISIK SEDIAAN PATCH EKSTRAK ETANOL DAUN KUMIS KUCING (Orthosiphon stamineus) - Arfiani Arifin; Muhammad Iqbal (Jurnal Ilmiah Manuntung, 2019)
Various forms of medicine can provide options for using drugs to the public such as patch. The research purpose was to determine variation concentration of Polyvinylpirolidone (PVP) and Ethyl cellulose (EC) as polymer patch which obtain the best physical characteristics of the Orthosiphon stamineus leaves ethanol extract patch. The ethanol extract of Orthosiphon stamineus leaves was obtained through maceration method using 70% ethanol solvent. The extract was formulated in the form of patch using the solvent casting method. The result showed that the best physical characteristics patch formulation was the F3 formula (250 mg of EC and 25 mg of PVP) with organoleptic test (a brownish green color, square shape and characteristic odor), patch humidity ( 3,64%), the average weight uniformity test (0.567 gram ± 0.01) and the patch thickness test (0.375 mm ± 0.02).